Creating The Documentary Film “Main Hang On – Pasar Sadar Titi Papan” Using An Expository Style - Sri Wahyuni (Perkumpulan Program Studi Film dan Televisi Indonesia, 2022)
The documentary film “Main Hang On - Pasar Sadar Titi Papan” aims to demonstrate the current state of traditional markets following the pandemic that has lasted for around two years through a documentary film. Through an expository style, the audiences are provided with clear information on the livelihood of merchants in traditional markets. The use of narration aids comprehension of the narrative. In addition, the story’s portrayal of causality and difficulties has been made more explicit. The creation of this documentary film began with pre-production (research: literature review, observation, and interviews), followed by production and post-production. In order to provide information about the Pasar Sadar Titi Papan, the concept behind this documentary’s production employed technical and aesthetic concepts by including voice-over components. Moreover, the interview scenes were performed with several market merchants who spoke about market activities, the buying and selling procedure, and their decreased revenue due to an increasing number of people switching to online shopping. The final product is an expository-style documentary film.